2022
DOI: 10.1007/s11077-022-09468-0
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the use of knowledge in policymaking: barriers and facilitators from a subjectivist perspective (1990–2020)

Abstract: The use of knowledge and evidence in policymaking is a recurrent topic of research due to its scientific and policy relevance. The existing and expansive body of literature has been scrutinised in various ways to grasp the dimensions of knowledge utilisation in policymaking, although most of this research has a monosectoral focus and is based on very general criteria of analysis that do not completely account for the complexity of policy making. This paper overcomes this limitation by enlightening the epistemo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 67 publications
0
11
0
Order By: Relevance
“…To summarize, knowledge must either be for or in policymaking. 4 The existence of this debate indicates two fundamental and connected concepts whose understanding may prove useful to the disaster research community. These concepts are that knowledge has a "shape," and that policymakers are human and sensitive to the shape of knowledge.…”
Section: Current Scholarship On the Academic Knowledge-policymaking R...mentioning
confidence: 99%
See 2 more Smart Citations
“…To summarize, knowledge must either be for or in policymaking. 4 The existence of this debate indicates two fundamental and connected concepts whose understanding may prove useful to the disaster research community. These concepts are that knowledge has a "shape," and that policymakers are human and sensitive to the shape of knowledge.…”
Section: Current Scholarship On the Academic Knowledge-policymaking R...mentioning
confidence: 99%
“…Unfortunately, evidence type seems to have little effect on its acceptance compared to policymakers' ideations. 4 Even so, we should continue trying to communicate knowledge, so how? What shape should disaster research take to facilitate its application to policy?…”
Section: Disaster Research Knowledge "Shape"mentioning
confidence: 99%
See 1 more Smart Citation
“…This special issue is rich of learning on these two levels. In an era in which evidence-based policy is increasingly a mantra (Capano & Malandrino, 2022), Kurzer and Ornston (2023) urge policymakers to be cautious with applying what scientific advisors recommend in times of high uncertainty. Their contribution aims to explain the results of previous large-n studies that found integrating scientific knowledge into policymaking can slow down the response to the pandemic.…”
mentioning
confidence: 99%
“…This overall literature has been reviewed and summarized in several different ways. Many reviews synthesize upshots for research-policymaking relations from this broad literature (e.g., Blake & Ottoson, 2009; Capano & Malandrino, 2022; French, 2018; B. Head, 2016; Newman, 2020).…”
mentioning
confidence: 99%